Implementation of Information System in Indonesian Traditional Beverage Businesses - Hadi Purnomo; F R Fitrah; R Maulana; M M Pratadina (Universitas Komputer Indonesia, 2021)
This study aims to apply the information system to every business owner who can inform businesses beverage container business through information technology. The function of this information system's application is for business owners and customers interested in buying products business. This study is an application of information systems in the Indonesian Traditional Beverage Business. This study's method was conducted using qualitative descriptive writing method of collecting data through literature study and observation to the growing beverage business owners. Information system development is conducted using the waterfall method. The results of this study show an overview of how the information system is expected by the business owner as well as the beverage business impact that can provide the quality of the business product beverage business is being run. The conclusion is that there is a large information container such as a website application applied to the Indonesian traditional beverage business so that website visitors can see, buy, or provide suggestions or comments regarding the already available products